Freaks of the heartland - Niles, Steve (Dark Horse Books, 2021)
"Trevor's monstrous little brother lives in the barn behind the house. The boy's only six years old, but he towers over his older brother, and possesses incredible strength. For years, Trevor has looked after his baby brother, keeping him from the light, but now that's all about to change. His family's secret is about to be revealed, uncovering the horrible truth of the small midwestern town the boys have grown up in."--